중요목조문화재 안전경비인력 의식조사 연구 - 신호준; 구원회; 백민호 (한국재난정보학회 논문집, 9(2), 2013)
본 연구에서는 중요목조문화재를 직접 관리하고 있는 안전경비인력에 대한 제도를 검토하였고 전국 158개 중요목조문화재에 배치되어 있는 안전경비인력의 배치인원, 연령, 업무, 교육 및 훈련에 대한 현황을 조사하였다. 또한 의식조사를 통해 안전경비인력의 배치인원, 연령, 교육 및 훈련 내용, 범위 등의 인프라에 대한 세부 기준이 없는 문제점을 도출하여 향후 목조문화재 방재대책 수립 시 발전방향을 제시하였다. This research examined the business system and current status of the safety security manpower managing directly important wooden cultural heritage and grasped on the current situation of arrangement, age, and duties of safety security manpower arranged in 158 important wooden cultural heritages. Also, it intends to highlight the current status and implications of safety security and suggest developmental direction for the establishment of wooden cultural heritages preventive measures in the future. KCI Citation Count: 0